TINJAUAN YURIDIS TERHADAP KEDUDUKAN ALAT BUKTI ELEKTRONIK BERDASARKAN PUTUSAN MK NOMOR 20/PUU-XIV/2016 - I Nengah Ariana (LPPM Universitas Ekasakti Padang, 2022)
Information technology plays an important role for the present and the future which in itself changes people's behavior. Information technology contributes to the law of evidence in Indonesia with the recognition of electronic evidence. In 2016, the Constitutional Court of the Republic of Indonesia issued the Constitutional Court Decision Number 20/PUU-XIV/2016 which had a juridical impact on changing the definition of legal electronic evidence. This decision is considered contrary to the spirit of the ITE Law and causes a blurring of norms regarding the legal position of electronic evidence. The purpose of this study is to examine the legal regulation of the position of electronic evidence and the legal consequences of the Constitutional Court's decision Number 20/PUU-XIV/2016. This research is classified as qualitative research with a normative juridical method, so that the sources used come from library data, both primary, secondary, and tertiary legal sources. The results of this study state that the legal arrangement for the position of electronic evidence in Indonesia in the ITE Law has changed since the Constitutional Court Decision Number 20/PUU-XIV/2016 which has provided an interpretation of the phrase electronic information and/or electronic documents in article 5 paragraph (1) and paragraph (2), and article 44 letter b of the ITE Law regarding the provisions of legal evidence and has implications for the function of electronic evidence in criminal law, namely the emergence of legal uncertainty over the validity of electronic evidence in court and the occurrence of differences in interpretation in law enforcement.